PSYCHOLOGICAL, THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF REPRODUCTIVE CULTURE - Mamatova Nafisa; Khujamberdiyeva Hamidaxan (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this article contains certain grounds for the development of theoretical, methodological and practical aspects of the study of reproductive culture, which make it possible to obtain a holistic view of reproductive culture, which cannot be achieved within the framework of the methodology of scientific knowledge. The article provides information about reproductive culture, trends in its development and analysis of transmission mechanisms.